2020
DOI: 10.3390/molecules25173931
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing the Chemical Stability and NMR Parameters of Uracil Tautomers and Its 5-Halogen Derivatives

Abstract: We report on the density functional theory (DFT) modelling of structural, energetic and NMR parameters of uracil and its derivatives (5-halogenouracil (5XU), X = F, Cl, Br and I) in vacuum and in water using the polarizable continuum model (PCM) and the solvent model density (SMD) approach. On the basis of the obtained results, we conclude that the intramolecular electrostatic interactions are the main factors governing the stability of the six tautomeric forms of uracil and 5XU. Two indices of aromaticity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…1 mg/mL [18]) and its solutions are often prepared in strongly basic media which also increases the side effects of the treatment [19]. The molecule of 5-FU, as a typical pyrimidine base, is subject to tautomeric equilibria between several structural isomers (NH/OH tautomers) [20][21][22]. Despite the possible existence of six tautomers, only one of them (diketo C=O/C=O form, see Figure 1a) is present practically exclusively in aqueous solutions [23] and this isomer is active as a chemotherapeutic agent [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…1 mg/mL [18]) and its solutions are often prepared in strongly basic media which also increases the side effects of the treatment [19]. The molecule of 5-FU, as a typical pyrimidine base, is subject to tautomeric equilibria between several structural isomers (NH/OH tautomers) [20][21][22]. Despite the possible existence of six tautomers, only one of them (diketo C=O/C=O form, see Figure 1a) is present practically exclusively in aqueous solutions [23] and this isomer is active as a chemotherapeutic agent [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Uracil is an important component related to information transfer and replication in living systems. Its 5-halogen modifications are used in anticancer and antifungal treatment [ 59 , 61 , 62 , 63 ]. Modifications of uracil, including replacing the oxygen atom with sulfur [ 64 ], also changes its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…1a, is most stable. [16][17][18][19] According to X-ray studies, uracil is found only in the diketo form in the solid phase, and in the same form, it exists in water. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%